Multiple Interfaces of Big Pharma and the Change of Global Health Governance in the Face of HIV/AIDS - Jan Peter Wogart (German Institute of Global and Area Studies (GIGA), 2006)
By using a game theoretical approach and the notion of 'forum' or 'regime shifting' this paper examines the multiple interfaces of the multinational pharmaceutical corporations (MNPCs) with their major counterparts at home and abroad, including the governments of the North and South, the international organizations and increasingly with national and international NGOs in the context of the spreading HIV/AIDS crisis. It shows how the execution of the MNPCs' strategies led to significant reactions from other actors, which led to further moves and countermoves in a strategic battle between representatives of the North and the South in the global health arena. – – Der Text analysiert die Interaktionen zwischen den Multinationalen Pharmazeutischen Unternehmen (MNPCs) und den Regierungen der Industrie- und Entwicklungsländer, sowie den internationalen Organisationen und den Nichtregierungsorganisationen im Zusammenhang mit der weltweiten Verbreitung der HIV/AIDS-Krankheit. Die Analyse zeigt, wie die zahlreichen anfänglichen Konflikte an allen Fronten in den letzten Jahren mehr und mehr durch Kompromisse und gemeinsame Initiativen ersetzt wurden, die die Architektur der 'Global Health Governance' entscheidend verändert haben.
Keywords: I; K; 330; Multinational Pharmaceutical Corporations (MNPCs); HIV/AIDS; global health governance; pricing of ARVs; Global Governance; Gesundheit; Gesundheitsversorgung; AIDS; Pharmazeutische Industrie; Multinationales Unternehmen; Welt